1975
DOI: 10.1007/bf02532701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary safflower oil upon lipogenesis in neonatal lamb

Abstract: The effect of dietary safflower oil upon lipogenesis has been investigated in neonatal lambs. Preliminary experiments with lambs suckled by their mothers showed that there was a 10-fold increase in the rate of incorporation of [14-C] from acetate into fatty acids in adipose tissue slices during the first 10 days post partum. Barely detectable rates of [14-C] acetate incorporation into fatty acids were found in liver slices from lambs during the same period. In lambs given cows' milk from birth untill 11 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…mg protein-', at 3O'C) [6]. In addition only 19% of the PDH in sheep adipose tissue was in the active state compared with 40-50% in adipose tissue from rats fed normal chow [8], but this is similar to the proportion of PDH in the active state in fasted or diabetic rats or rats fed a high fat diet for 6 days (12-18%) [6]. Adipose tissue from rats in these latter stat& has a low rate of fatty acid synthesis from glucose and a relatively high proportion of glucose utilized is released from the tissue as lactate [6,11,12].…”
Section: Adipose Tissuementioning
confidence: 94%
See 1 more Smart Citation
“…mg protein-', at 3O'C) [6]. In addition only 19% of the PDH in sheep adipose tissue was in the active state compared with 40-50% in adipose tissue from rats fed normal chow [8], but this is similar to the proportion of PDH in the active state in fasted or diabetic rats or rats fed a high fat diet for 6 days (12-18%) [6]. Adipose tissue from rats in these latter stat& has a low rate of fatty acid synthesis from glucose and a relatively high proportion of glucose utilized is released from the tissue as lactate [6,11,12].…”
Section: Adipose Tissuementioning
confidence: 94%
“…Protein concentration of the homogenates was determined by the method in [7]. The rate of incorporation of 14C from [U-14C]glucose into fatty acids in sheep adipose tissue slices was measured as in [8] except that the incubation medium (Krebs-Ringer bicarbonate) contained 3 mM glucose, 0.6 mM acetate, 1 mM L-lactate and 0.1 pg . ml-' insulin.…”
Section: Materials Aud Methodsmentioning
confidence: 99%
“…Moore & Christie (1984) suggested that when ruminants are fed large quantities of unsaturated fats (as in the present study) the hydrogenation capacity of the rumen is exceeded. The changes in fatty acid composition of some tissues were described in lambs fed PUFA-supplemented diets (Vernon, 1975;Muci et al, 1992a;Enser et al, 1998). Chang et al (1992) concluded that the unsaturated fatty acid composition of the ruminant tissues may be modified through the diet if the fatty acids escaped ruminal changes.…”
Section: Resultsmentioning
confidence: 99%
“…However. in neonatal animals celiular hypertrophy and &a;ked variations'in adipocyte sizes in animals of the same chronological age can complicate the evaluation of age-related changes in adipose tissue metabolism (3,15). Fat cells from fetal calves can be expected to be smaller than those of newborn calves (3).…”
Section: Glycerol For Fatty Acid Esterification Pentose Phosphatementioning
confidence: 99%